2019
DOI: 10.3389/fpsyg.2018.02682
|View full text |Cite
|
Sign up to set email alerts
|

How Live Music Moves Us: Head Movement Differences in Audiences to Live Versus Recorded Music

Abstract: A live music concert is a pleasurable social event that is among the most visceral and memorable forms of musical engagement. But what inspires listeners to attend concerts, sometimes at great expense, when they could listen to recordings at home? An iconic aspect of popular concerts is engaging with other audience members through moving to the music. Head movements, in particular, reflect emotion and have social consequences when experienced with others. Previous studies have explored the affiliative social e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 86 publications
3
93
0
2
Order By: Relevance
“…Recently, research on audiences of live performances has gained interest in part because group of spectators provide a valid and ecological setting for investigate group dynamics during collective experiences. In particular, physiological synchrony between audience members and performers has been found to be influenced by spectators' artistic preference 41 , subjective attentional modulation 42 and intersubjective engagement 43 . Similarly, spectators' enjoyment during a live dance performance seems to be sensitive to how dancers coordinate and synchronized their movements, rather than how much they move 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research on audiences of live performances has gained interest in part because group of spectators provide a valid and ecological setting for investigate group dynamics during collective experiences. In particular, physiological synchrony between audience members and performers has been found to be influenced by spectators' artistic preference 41 , subjective attentional modulation 42 and intersubjective engagement 43 . Similarly, spectators' enjoyment during a live dance performance seems to be sensitive to how dancers coordinate and synchronized their movements, rather than how much they move 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This result is not in line with the findings of Jenna and Silverman, who concluded that live music seems to be effective in reducing pain. Swarbrick et al also determined that live music engages listeners to a greater extent than pre‐recorded music. However, Lee illustrated that there was no statistical difference between MM and MT ( P = 0.23) in their meta‐analysis, but that both music interventions played a vital role in benefitting patients in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the competition timing, we could not gather the opinions of all respondents regarding the wearable devices: this meant we were unable to correlate the agreement of the participants and scales. Finally, since one aim of the study was to evaluate the feasibility of neurophysiological recordings in natural conditions, we did not record audio and video motion that would be appropriate for study of the orchestra and public (Swarbrick et al, 2019). Audio and video motion, combined with neurophysiological recordings, could offer a unique approach in the understanding of emotional synchronization and should be included in future research.…”
Section: Limitationsmentioning
confidence: 99%
“…Most people listen to music for its emotional effect (Nieminen et al, 2012) and research has shown the pleasurable effect of music (Grewe et al, 2007;Salimpoor et al, 2009Salimpoor et al, , 2011. The social connection with other people and being connected to the performers are the main factors that motivate people to attend live performances and enjoy them (Burland and Pitts, 2014;Leante, 2016;Swarbrick et al, 2019). Music is a form of cultural communication (McCormick, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation